PENEGAKAN HUKUM PIDANA TERHADAP PENCEMARAN LINGKUNGAN DISUNGAI SIAK BERDASARKAN UNDANG UNDANG NO 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Tiara Aria Wulandari Sitanggang; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One of the environmental pollution is water pollution through river, as happened in Siak River. The level of contamination of the Siak River, is increasingly alarming. Siak River has been proven to be polluted but Environmental Cultivation Enforcement in Siak River is not running maximally. Firstly to know the law enforcement process and the implementation of sanctions that must be done law enforcement officers in handling environmental pollution that occurred in Siak River, Second to know the cause of its slow and not terebut enforcement of environmental crime law regarding environmental pollution that occurred in Siak River. Third to find out what efforts can and should be done by the government and law enforcement officers so that environmental pollution in the siak river can be quickly resolved.This type of research can be categorized in the type of sociological research. The research location is Riau Province Environmental Agency (BLH) and Riau Regional Police. Data source used is primary data and secondary data. Data collection techniques are interviews, questionnaires and literature reviewFrom the research there are three main points that can be concluded. First, the implementation of environmental criminal law enforcement by the Environment Agency (BLH) of Riau Province and the Directorate of Riau Police Reskrimsus against perpetrators of destruction and pollution of the environment is done by preventive and repressive. Both obstacles faced by the Directorate of Riau Province Police Reskrimsus and Environment Agency (BLH) in the enforcement of environmental criminal law is the discovery of internal and external constraints. The three efforts undertaken by Ditreskrimsus Polda Riau and Environment Agency (BLH) Riau Province is supposed to overcome obstacles both in terms of Internal and externalKeywords: Environmental Pollution - Law Enforcement - Siak River